Different pain phenotypes are associated with anti-Caspr2 autoantibodies. - Greguletz, Patrik; Plötz, Maria; Baade-Büttner, Carolin; Bien, Christian G.; Eisenhut, Katharina; Geis, Christian; Handreka, Robert; Klausewitz, Jaqueline; Körtvelyessy, Peter; Kovac, Stjepana; Kraft, Andrea; Lewerenz, Jan; et al. (Journal of Neurology, 2024)
Autoantibodies against contactin-associated protein 2 (Caspr2) not only induce limbic autoimmune encephalitis but are also associated with pain conditions. Here, we analyzed clinical data on pain in a large cohort of patients included into the German Network for Research in Autoimmune Encephalitis. Out of 102 patients in our cohort, pain was a frequent symptom (36% of all patients), often severe (63.6% of the patients with pain) and/or even the major symptom (55.6% of the patients with pain). Pain phenotypes differed between patients. Cluster analysis revealed two major phenotypes including mostly distal-symmetric burning pain and widespread pain with myalgia and cramps. Almost all patients had IgG4 autoantibodies and some additional IgG1, 2, and/or 3 autoantibodies, but IgG subclasses, titers, and presence or absence of intrathecal synthesis were not associated with the occurrence of pain. However, certain pre-existing risk factors for chronic pain like diabetes mellitus, peripheral neuropathy, or preexisting chronic back pain tended to occur more frequently in patients with anti-Caspr2 autoantibodies and pain. Our data show that pain is a relevant symptom in patients with anti-Caspr2 autoantibodies and support the idea of decreased algesic thresholds leading to pain. Testing for anti-Caspr2 autoantibodies needs to be considered in patients with various pain phenotypes.
EVALuna2:556171